Immune Cell–Specific SMN Expression and Sustained Immune Alterations in Treated Spinal Muscular Atrophy - Ines Tapken; Katharina Rahmel-Stein; Christine Ehlers; Federica Cieri; Nora T. Detering; Tobias Schüning; Bogdan Bjelica; Charlotte Mindermann; Svenja Neuhoff; Linda-Isabell Schmitt; Markus Leo; Tim Hagenacker; et al. (Journal of Clinical Investigation, 2026)
Mutations in the survival of motor neuron 1 ( SMN1 ) can reduce functional SMN protein levels, which causes Spinal Muscular Atrophy (SMA), a disease affecting the nervous system and peripheral tissues, including the immune system. Yet, SMN expression across immune cell subsets and the impact of SMN-modulating therapies on the immune system remains underexplored. We found that in neonatal mouse spleen, SMN expression was highest in B cells, which were massively reduced in SMA mice. In human PBMCs from adults, DCs and monocytes expressed the highest SMN levels, whereas SMA patients showed reduced DC and increased B cell frequencies. Patients receiving systemic versus CNS-restricted therapy showed similar differences in immune cell composition and SMN levels. Similarly, an exploratory cohort including untreated patients did not indicate a substantial treatment-specific effect relative to controls. To assess the impact of differentiation on SMN, PMA-treated THP-1 cells were analyzed, revealing enhanced aberrant SMN splicing and increased SMN-positive Cajal bodies. In conclusion, SMN levels vary across immune cell types, and reduced SMN levels are associated with altered immune cell composition. Immune alterations and decreased SMN levels were observed in both treated and untreated SMA patients and may contribute to dysfunctions of the immune system in SMA.